Glanzmann's thrombasthenia - A rare case report of spontaneous gingival bleeding - Vijayalakshmi Venkat; Sruti Kalluri; Satheesha Reddy Bandalore Hanumantha (Wolters Kluwer Medknow Publications, 2018)
Glanzmann's thrombasthenia is a rare congenital bleeding disorder which is associated with mutations in the genes encoding glycoproteins, gpIIb or gpIIIa resulting in platelet dysfunction. Here we present a case of 10 years old female patient with spontaneous bleeding gums since 4 days seeking dental treatment. She was under medical supervision following a diagnosis of some bleeding disorder before 4 years. With careful early diagnosis and proper supportive care Glanzmann's thrombasthenia has a very good prognosis.